Genome-wide association study of prostate cancer in men of African ancestry identifies a susceptibility locus at 17q21. - Haiman, C. A.; Chen, G. K.; Tettey, Y.; Strom, S. S.; Berndt, S. I.; Kittles, R. A.; Isaacs, W.B.; Ingles, S.A.; Stanford, J.L.; Diver, W.R.; Witte, J.S.; Hsing, A.W.; et al. (My University, 2011)
In search of common risk alleles for prostate cancer that could contribute to high rates of the disease in men of African ancestry, we conducted a genome-wide association study, with 1,047,986 SNP markers examined in 3,425 African-Americans with prostate cancer (cases) and 3,290 African-American male controls. We followed up the most significant 17 new associations from stage 1 in 1,844 cases and 3,269 controls of African ancestry. We identified a new risk variant on chromosome 17q21 (rs7210100, odds ratio per allele = 1.51, P = 3.4 × 10(-13)). The frequency of the risk allele is ∼5% in men of African descent, whereas it is rare in other populations (<1%). Further studies are needed to investigate the biological contribution of this allele to prostate cancer risk. These findings emphasize the importance of conducting genome-wide association studies in diverse populations.